Exploring Innovations in Teaching, Assessment, and Technology for English Language Education in Indonesian Tertiary Education - Islami, Annisa Permata; Putri, Syadza Adila; Hasibuan, Hapni Nurliana H.D (FKIP - Universitas Riau, 2025)
Educational policy, technological advancement, and socio-cultural dynamics in Indonesia have made English language learning increasingly complex. Therefore, appropriate strategies are required in selecting teaching methods, assessments, and technology to ensure that the learning process remains effective and adaptive to these changes. This study employs a qualitative approach with a case study design to explore the implementation of teaching methods, assessments, and technology in English language learning in Indonesia. Data were collected from six lecturers at a university in Indonesia through onsite and online interviews, observations, and document analysis. The findings reveal that the implementation of English language teaching is influenced by educational policies, cultural factors, and student characteristics. The implementation of the Outcome-Based Education (OBE) policy encourages the use of active learning approaches such as Project-Based Learning (PBL) and cooperative learning, which emphasize learning outcomes. In addition, assessment forms are aligned with the adopted teaching methods, allowing evaluations to better reflect students’ learning processes and achievements. The use of technology also plays a crucial role in providing interactive and flexible learning experiences while facilitating assessment practices. Overall, this study highlights the importance of integrating teaching methods, assessments, and technology within the context of educational policy and local culture. These findings are expected to contribute to the development of more contextual and relevant strategies for English language teaching in Indonesia.